Human Rights Standards Hegemony, Law, and Politics - Mutua, Makau (SUNY series, Praxis: Theory in Action, 2016)
Analyzing the confluence between coloniality and activist art, Art Activism for an Anticolonial Future argues that there is much to gain from approaching contemporary politically committed art practices from the angle of anticolonial, postcolonial, and decolonial struggles. These struggles inspired a vast yet underexplored set of ideas about art and cultural practices and did so decades before the acceptance of radical artistic practices by mainstream art institutions. Carlos Garrido Castellano argues that art activism has been confined to a limited spatial and temporal framework-that of Western culture and the modernist avant-garde. Assumptions about the individual creator and the belated arrival of derivative avant-garde aesthetics to the periphery have generated a narrow view of "political art" at the expense of our capacity to perceive a truly global alternative praxis. Garrido Castellano then illuminates such a praxis, focusing attention on socially engaged art from the Global South, challenging the supposed universality of Western artistic norms, and demonstrating the role of art in promoting and configuring a collective critical consciousness in postcolonial public spheres.This book is freely available in an open access edition thanks to Knowledge Unlatched-an initiative that provides libraries and institutions with a centralized platform to support OA collections and from leading publishing houses and OA initiatives. Learn more at the Knowledge Unlatched website at: https://www.knowledgeunlatched.org/, and access the book online at the SUNY Open Access Repository at http://hdl.handle.net/20.500.12648/7166